Metaphors, Models, and Flows: Elements for a Cartography of Technology In Learning - Ruben R. Puentedura (2011)

Metaphors, Models, and Flows: Elements for a Cartography of Technology In Learning - Ruben R. Puentedura (2011)
The slides for my November 23-25 sessions in Malmö, Göteborg, and Stockholm

SAMR and TPCK: A Workshop - Ruben R. Puentedura (2011)